Klebsiella pneumoniae necrotizing fasciitis of the leg in an elderly French woman - Monié M (Dove Medical Press, 2014)
Marguerite Monié,1 Laurence Drieux,2–4 Bernadette Nzili,1 Michèle Dicko,5 Catherine Goursot,1 Sandrine Greffard,6 Dominique Decré,3,4,7 Anthony Mézière1 1Assistance Publique-Hôpitaux de Paris (AP-HP), GHU Pitié Salpêtrière-Charles Foix, site Charles Foix, Service de Soins de Suite et Réadaptation orthogériatrique et polyvalent, Fondation d’Heur et Chemin Delatour, Ivry s/Seine, 2Assistance Publique-Hôpitaux de Paris, Hôpital Charles-Foix, Bactériologie-Hygiène, Paris, 3Sorbonne Universités, UPMC Univ Paris 06, CR7, Centre d’Immunologie et des Maladies Infectieuses, CIMI, team E13 (Bacteriology), Paris, 4INSERM, U1135, Centre d’Immunologie et des Maladies Infectieuses, CIMI, team E13 (Bacteriology), Paris, 5AP-HP, GHU Henri Mondor, Département de Médecine Interne et Gériatrie, Créteil, 6AP-HP, GHU Pitié Salpêtrière-Charles Foix, site Pitié Salpêtrière, Service de Médecine Gériatrique, Paris, 7AP-HP, Hôpital Saint-Antoine, Bactériologie-Hygiène, Paris, France Abstract: Klebsiella pneumoniae necrotizing fasciitis is a rare infection in regions outside of Asia. Here, we present a case of necrotizing fasciitis of the leg caused by K. pneumoniae in a 92-year-old French woman hospitalized in a geriatric rehabilitation unit. The patient initially presented with dermohypodermitis of the leg that developed from a dirty wound following a fall. A few hours later, this painful injury extended to the entire lower limb, with purplish discoloration of the skin, bullae, and necrosis. Septic shock rapidly appeared and the patient died 9 hours after the onset of symptoms. The patient was Caucasian, with no history of travel to Asia or any underlying disease. Computed tomography revealed no infectious metastatic loci. Blood cultures showed growth of capsular serotype K2 K. pneumoniae strains with virulence factors RmpA, yersiniabactin and aerobactin. This rare and fatal case of necrotizing fasciitis caused by a virulent strain of K. pneumoniae occurred in a hospitalized elderly woman without risk factors. Clinicians and geriatricians in particular should be aware of this important albeit unusual differential diagnosis. Keywords: necrotizing fasciitis, Klebsiella pneumoniae, elderly